Pathological conditions of avian coccidiosis in the small scale commercial broiler farms in Dinajpur district - Hossain, Md Manik; Hossain, Md Shahadat; Mussa, Md Tareq; Rashid, SM Harunur; Islam, Md Nazrul (Research in Agriculture Livestock and Fisheries, 2016)
The study was designed to investigate the pathological conditions of avian coccidiosis in the small scale commercial broiler farms at different region in Dinajpur district during July, 2012 to December, 2012. A thorough clinical and necropsy examination was done and the characteristics clinical signs and gross lesions were recorded. Different organs mainly caecum and other parts of intestine were collected, preserved and processed for histopathological examination. Intestinal content was also examined for detection of oocyst. Total 234 diseased and dead birds (from 50 farms) were examined out of which 20 (8.54%) birds were found to be positive for coccidiosis. The clinical signs of the affected birds were bloody diarrhea, anemia, reduction of feed and water intake, drooping wings. At necropsy, enlargement and discoloration of caecum with numerous hemorrhagic spots, blood mixed and reddish to brown intestinal contents in the intestinal lumen, hemorrhage on the intestinal wall and mucosa were found. Histopathological examination revels distortion of normal architecture of intestine and desquamation of lining epithelia, formation of tissue debris on the intestinal mucosa and necrotic cells infiltration in the lamina propria and submucosa, degeneration of epithelial cells, glands and intestinal villi. So, outbreaks of coccidiosis in the commercial poultry flocks in Dinajpur district is lower due to farmers are intensely aware of coccidiosis now and they usually use coccidiostats routinely. Res. Agric., Livest. Fish.3(3): 425-431, December 2016